Ion acceleration in scanning wake-fied accelerator - Latsko, E.M. (Вопросы атомной науки и техники, 2003)
We propose a concept of high-gradient acceleration in a Scanning Wake-Field Accelerator (SWFA). Advantages inherent to this concept make it possible to create a compact accelerator with a stable, long-duration and controlled acceleration in a wide range of velocities, that is very significant for ion acceleration with a small ratio Zi/Mi (Zi is the ionization state, Mi – ion mass).